Adverse events in healthy subjects exposed to single and multiple doses of LY2140023 monohydrate: pooled results from 10 phase 1 studies - Ayan-Oshodi, Mosun; Wondmagegnehu, Eshetu T; Lowe, Stephen L; Kryzhanovskaya, Ludmila; Walker, Daniel J; Kinon, Bruce J (Journal of clinical psychopharmacology, 2012)
Ten phase 1 studies of LY2140023 monohydrate (LY2140023), an mGlu2/3 receptor agonist, in healthy male and female subjects were pooled to evaluate the adverse event profile. These studies included both single-dose (5-200 mg) and multiple-dose (20-160 mg 2 times a day) treatment groups. The percentage of subjects reporting treatment-emergent adverse events (TEAEs) were assessed in placebo and LY2140023 dose groups: 5 to 20, 40, 60 to 80, and more than 80 mg (120-200 mg). The severity and duration of TEAEs were also determined. Electroencephalograms were performed in 1 study to detect if there were any prodromal signs of convulsions or seizures. Subjects who received either placebo or LY2140023 and participated in the single-dose (n = 159) and multiple-dose (n = 102) treatment groups were included in these analyses. No clear trends for increased TEAE incidence occurred with higher doses of LY2140023 in both the single-dose and multiple-dose treatment groups. The TEAEs with the highest incidence were gastrointestinal and nervous system events. No serious adverse events occurred in any of the 10 studies, and most TEAEs were mild in severity and transient in nature. There were no clinically significant changes in electroencephalograms in subjects receiving LY2140023 (n = 26). LY2140023 was generally well tolerated in healthy subjects.